Personality does not predict individual niche variation in a freshwater fish. (28th November 2020) - Kerr, Nicky R; Ingram, Travis
Abstract: Animal populations can exhibit considerable interindividual variation in both behavioral traits and niche use, but the potential connections between these characteristics are rarely compared for the same individuals. We aimed to test whether behavioral syndromes were predictive of individual diet or microhabitat in a native New Zealand freshwater fish, Gobiomorphus cotidianus . We carried out laboratory behavioral assays and repeated habitat and diet measurements in a seminatural mesocosm system. We found considerable repeatability in individual behavior, largely consistent with a proactive/reactive behavioral syndrome. We also found modest individual repeatability in microhabitat use and relatively strong individual specialization in diet. However, no measure of niche use in the mesocosms was significantly predicted by individual personality. Further studies of this type will be needed to assess whether links between individual behavior and resource use are more important in other species or ecological contexts. Abstract : Individuals in animal populations usually have distinct behaviors or personalities and also use resources in different ways. We tested whether the personality of individuals predicted their resource use in a freshwater fish, the common bully. Individuals varied in behavior, as well as in the use of different habitats and food types in outdoor tanks. However, personality did not predict individual resource use, showing that different facets of individuality are not always related.